Polypeptide Nanogels With Different Functional Cores Promote Chemotherapy of Lung Carcinoma - Niu, Kai; Li, Nan; Yao, Yunming; Guo, Chunjie; Ge, Yuanyuan; Wang, Jianmeng (Frontiers in Pharmacology, 2019)
Two kinds of tumor microenvironment-responsive polypeptide nanogels were developed for intracellular delivery of cytotoxics to enhance the antitumor efficacies and reduce the side effects in the chemotherapy of lung carcinoma. The sizes of both DOX-loaded nanogels methoxy poly(ethylene glycol)−poly(L-phenylalanine-co-L-cystine) (mPEG−P(LP-co-LC)) and methoxy poly(ethylene glycol)−poly(L-glutamic acid-co-L-cystine) (mPEG−P(LG-co-LC)) (NGP/DOX and NGG/DOX) were less than 100 nm, which was appropriate for the enhanced permeability and retention (EPR) effect. The loading nanogels were stable in the neutral environment while quickly degraded in the mimic intracellular microenvironment. Furthermore, the DOX-loaded reduction-responsive nanogels showed significantly higher tumor cell uptake than free DOX·HCl as time went on from 2 to 6 h. In addition, these DOX-loaded nanogels showed efficient antitumor effects in vivo, which was verified by the obviously increased necrosis areas in the tumor tissues. Furthermore, these DOX-loaded nanogels efficiently reduced the side effects of DOX. In conclusion, these reduction-responsive polypeptides based nanogels are suitable for the efficient therapy of lung carcinoma.